A Study of Antifungal Activity of Chrysophanol from Trichoderma viride Against some Phytopathogenic Fungi - Al-Aaraji, Alaa Mohsin (Iraqi Journal of Science, 2025)
This work aimed to evaluate the antifungal activity of chrysophanol derived from Trichoderma viride against some plant pathogenic fungi. A total of 160 infected plant samples were collected during the agricultural season of 2020-2021 from six plastic houses: two plastic houses (tomato plants) in Al-Rashidiya district, two plastic houses (eggplant plants) in Al-Nahrawan district and two plastic houses (cucumber plants) in Abu Ghraib district, Baghdad governorate. Five species of phytopathogenic fungi were isolated from infected plants and identified depending on morphological and microscopic characteristics. The results of microscopic examination showed that there were two species (Fusarium oxysporum and Rhizoctonia solani) from the Al-Rashidiya tomato field, three species (Fusarium solani, R. solani, and Sclerotinia sclerotiorum) from Al-Nahrawan eggplant field and three species from Abu Ghraib cucumber field (F. oxysporum, R. solani, and Pythium aphanidermatum). Among 160 infected plant samples, there were 42 isolates of F. oxysporum, 24 isolates of F. solani, 54 isolates of R. solani, 14 isolates of S. sclerotiorum, and 26 isolates of P. aphanidermatum. All isolates were subjected to a pathogenicity test by exposing sterilized local cress seeds to phytopathogenic fungal isolates. The results of this test showed moderate to high pathogenicity, but only 32 isolates recorded 100% pathogenicity, and 15 isolates from these isolates were selected for the antifungal test. Thirty Trichoderma spp. isolates were collected from the soil of three agriculture regions: Al-Rashidiya, Al-Nahrawan , and Abu Ghraib districts, and they were identified morphologically. These isolates were processed with ethyl acetate using the standard extraction method and then screened for producing chrysophanol by High-performance liquid chromatography (HPLC). The results showed that only 11 isolates produced chrysophanol, and isolate number 10 (Trichoderma viride) produced higher chrysophanol (7.74μg/ml) than the rest. Chrysophanol from T. viride was purified by preparative Thin-layer chromatography (TLC), and the final quantity was 6.5mg. Different concentrations of chrysophanol (20, 40, 80, and 120 ppm/ml) were prepared and then used against the isolated phytopathogenic fungi compared with the fungicide Beltanol at 40 ppm/ml. The chrysophanol concentrations 20, 40, and 80 ppm/ml significantly achieved a higher percentage of growth inhibition against S. sclerotiorum 1 followed by F. oxysporum 2, which recorded (48 and 44.75%) respectively, while P. aphanidermatum 2 was the least affected, which recorded 25%. The chrysophanol concentration of 120ppm/ml achieved 100% growth inhibition for all phytopathogenic fungi except for R. solani 2 and 5, which achieved 99%. Beltanol fungicide 40ppm/ml significantly achieved a higher percentage of growth inhibition against F. solani 4 followed by F. solani 1 recorded 94.25 and 93%, respectively, while S. sclerotiorum 1 was the least affected with 75.25% growth inhibition. When comparing the results of chrysophanol at the concentration of 80 ppm/ml with the concentration of 40ppm/ml of Beltanol fungicide, we noticed that chrysophanol is significantly superior to Beltanol in the percentage of growth inhibition of most of the phytopathogenic fungi under test. While at the concentration of 120 ppm/ml of chrysophanol, we noticed a significant superiority in the growth inhibition of all phytopathogenic fungi under this study, showing 100% growth inhibition. The results of the current study showed that chrysophanol from T. viride can be used as an effective fungicide to eliminate phytopathogenic fungi rather than the use of a chemical fungicide.